Essentials of pathophysiology concepts of altered health states - Porth, Carol (Wolters Kluwer/Lippincott Williams & Wilkins, 2011)
"Designed to present students with essential concepts of disease processes and altered health states, this third edition text is ideal for both discrete and integrated pathophysiology courses. The third edition continues to build on the extremely successful art program and the 'Understanding' feature and has an even more robust electronic support ancillary program to make both faculty and student learning easier and more successful"--Provided by publisher